Expression of Heterosis in Bivoltine Hybrids of Bombyx mori L. for Silk Yield Contributing Traits under Sub-tropical Conditions - Sajgotra, Mokshe; Bali, R. K. (International Journal of Bio-resource and Stress Management, 2023)
Synthesis of new-gene combinations by genetic manipulation is one of the powerful tools in exploiting the commercial qualities of plants and animals. The fundamental aim of silkworm breeding is to get robust and sturdy silkworm larvae for easy rearing and production of quality cocoon crop. Bivoltine breeds and hybrids excel in quality and productivity but do not display the crop stability. The main reason attributed to such instability is that the bivoltine breeds/hybrids suffer badly in adverse conditions. In the present study, an attempt was made to evaluate twenty-eight bivoltine hybrids raised by involving half (8×8) diallel set of bivoltine breeds including four hypersericigenous (PO1, PO3, ND2 and ND5) and four thermotolerents (Udhey-1, Udhey-3, Udhey-4 and Udhey-6) along with ruling bivoltine hybrid, SH6×NB4D2in order to identify the thermotolerent, adaptable bi×bivoltine silkworm hybrids suited for sub-tropical climate. Observations were made on eight economically important traits namely, larval weight, crop weight, single cocoon weight, single shell weight, shell ratio, average filament length, non-breakable filament length and denier. The data was analyzed using Evaluation index (E.I.) method. Ten hybrid combinations recorded mean evaluation index (E.I.) values of >50 ranging from 51.13 to 63.35, whereas, control scored E.I. value of 49.22 only. Two hybrid combinations, ND5×PO1 (63.35) and ND2×Udhey-6 (60.12) recorded Average E.I. value >60 for all the characters under sub-tropical conditions.